Mapping the Landscape of Teaching Poetry in English Literature: A Bibliometric Analysis of Global Research Trends - Safriyani, Rizka; Kamila, Bintana Cahya (Universitas PGRI Adi Buana Surabaya, 2025)
The influence of poetry teaching on language development in the context of English literature education has been the subject of numerous studies. Nevertheless, there is a dearth of a comprehensive overview of scholarly publications in this field. This bibliometric study is designed to depict the research landscape on teaching poetry in English literature by identifying the co-occurring keywords, the most productive countries and most cited authors using VOSviewer. A total of 140 articles were examined, indicating that the research trajectory is in its early and developing stages. The results indicate that the common co-occurring words are qualitative, fiction, lesson, literary elements, and popular culture. Moreover, the United Kingdom was the most productive of the five countries in the dataset, with 176 publications. Australia (113), Hungary (27), and the Netherlands (27) followed. Furthermore, Weaven and Clark are the most influential authors, with eight subsequent publications referencing them. The results underscore the evolving integration of poetry into English language education, which technological advancements and multimedia integration have considerably impacted. However, the pedagogical potential of digital instruments in poetry instruction still necessitates further investigation. The study concludes by addressing the primary implications and constraints, guiding future research in the intersection of English language teaching, literature, and poetry.